Trichophyton rubrum Phenotypic Virulence Factors in Mexican Strains - Esther Conde-Cuevas; Rigoberto Hernández-Castro; Claudia Erika Fuentes-Venado; Roberto Arenas; María Guadalupe Frías-De-León; Gabriela Moreno-Coutiño; María Esther Ocharan-Hernández; Eunice D. Farfan-Garcia; Rodolfo Pinto-Almazán; Erick Martínez-Herrera (Biology)
(1) Background: T. rubrum is the most important agent in tinea pedis, tinea manuum, tinea cruris, tinea corporis, and even in subcutaneous dermatophytosis. T. rubrum must overcome several obstacles to adhere, grow, and invade the host, for which their virulence factors are important. Previous studies have demonstrated the capability of T. rubrum strains to produce proteases, phospholipases, hemolysins, and elastases. The aim of this work was the genotypic identification of clinical isolates of T. rubrum to subsequently determine production of the main phenotypic virulence factors associated with this pathogen responsible for different types of dermatophytosis in Mexican patients. (2) Methods: Twenty samples of T. rubrum were obtained from different body parts of patients treated in the Mycology section. The colonies were transferred to specific agars to analyze the production of phenotypical virulence factors (lipase, phospholipase, hemolysin, and elastase). (3) Results: Almost all the strains of T. rubrum showed growth in the test culture medium. A significantly smaller size of the halo diameter of elastase (26.51 ± 11.95 mm) in comparison to lipase (59.51 ± 16.00 mm) and phospholipase (55.97 ± 19.60 mm) was measured. Additionally, a significantly reduced size of the halo diameter of hemolysin (42.01 ± 5.49 mm) was observed compared to lipase. When comparing the virulence factors, greater expression of lipase was observed, followed by phospholipase, hemolysins, and elastase. T. rubrum strains were classified as being between high and ultra-lipase producers; most of the strains were also considered low producers of phospholipase and hemolysins; and most of the strains (n = 13) were classified as non-producers of elastase. (4) Conclusions: Almost all the T. rubrum strains of the study were found to be ultra-producers of lipase, and low producers of hemolysins and phospholipases. Elastase was the least expressed virulence factor in these strains.